2017
DOI: 10.1007/s40745-017-0122-3
|View full text |Cite
|
Sign up to set email alerts
|

Big Data and Causality

Abstract: Causality analysis continues to remain one of the fundamental research questions and the ultimate objective for a tremendous amount of scientific studies. In line with the rapid progress of science and technology, the age of Big Data has significantly influenced the causality analysis on various disciplines especially for the last decade due to the fact that the complexity and difficulty on identifying causality among Big Data has dramatically increased. Data Mining, the process of uncovering hidden informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 141 publications
0
18
0
Order By: Relevance
“…However, the energy consumption behaviour can be investigated by the big data analytics in micro level. Besides, a bunch of data mining techniques can be used to examine the causal relationship between variables (Hassani et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…However, the energy consumption behaviour can be investigated by the big data analytics in micro level. Besides, a bunch of data mining techniques can be used to examine the causal relationship between variables (Hassani et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…The era of big data came along with both big opportunities and challenges, almost all science subjects are experiencing overflowing information at unpredictable volume and speeds [1]. As such, revealing the hidden information in big data via Data Mining (DM) techniques has became an emerging trend and ultimate objective for a wide range of studies [2][3][4][5]. As a data intensive subject, banking has been a popular implementation field for researchers with DM skills over the past decades of the information science revolution.…”
Section: Introductionmentioning
confidence: 99%
“…Further, it is rather difficult to distinguish cyclic and seasonal components in the shorter duration data being used for SHM applications. In view of this, a majority of the research reported on SSA terms the cyclic and seasonal components together as oscillatory components . The eigenvectors obtained from SSA with a window size of 20 are plotted and shown in Figure .…”
Section: Numerical Studiesmentioning
confidence: 99%